2014
DOI: 10.1177/1470320313516172
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACE and MTHFR genetic polymorphisms with type 2 diabetes mellitus: Susceptibility and complications

Abstract: The MTHFR 677 TT genotype was associated with T2DM susceptibility and complications (DR, DPN and IHD). The MTHFR 1298 CC, AC and ACE DD genotypes were associated with DR and DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…Literature on the available previous studies, the two important polymorphisms of MTHFR gene 677 C>T and 1298 A>C genotypes were analyzed with PCR-RFLP technique using Hinf1 and MboII digestion, respectively. 15 The screening of C677T, PCR products was digested with 5U of HinfI at 37 C overnight. The 'C' allele gave 387 bp products, whereas the 'T' allele gave 235 bp and 152 bp fragments.…”
Section: Mthfr Markers and Genotypingmentioning
confidence: 99%
“…Literature on the available previous studies, the two important polymorphisms of MTHFR gene 677 C>T and 1298 A>C genotypes were analyzed with PCR-RFLP technique using Hinf1 and MboII digestion, respectively. 15 The screening of C677T, PCR products was digested with 5U of HinfI at 37 C overnight. The 'C' allele gave 387 bp products, whereas the 'T' allele gave 235 bp and 152 bp fragments.…”
Section: Mthfr Markers and Genotypingmentioning
confidence: 99%
“…Clinically, DR is divided into proliferative DR (PDR), preproliferative DR and nonproliferative DR (NPDR) [5]. Much evidence has suggested that genetic predisposition plays a role in the development and progression of DR [6][7][8]. The genetic etiology of DR was investigated by a candidate gene approach, and the potential candidate genes in DR etiology were implicated [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Numbers of molecular epidemiological studies have been performed to examine the relationship between the ACE I/D polymorphism and DR [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], but the results remain inconclusive. Although several meta-analyses have been published [56,57], they still did not reach a consistent conclusion.…”
Section: Introductionmentioning
confidence: 99%